2011
DOI: 10.1016/j.jcps.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A neural predictor of cultural popularity

Abstract: We use neuroimaging to predict cultural popularity -something that is popular in the broadest sense and appeals to a large number of individuals. Neuroeconomic research suggests that activity in reward-related regions of the brain, notably the orbitofrontal cortex and ventral striatum, is predictive of future purchasing decisions, but it is unknown whether the neural signals of a small group of individuals are predictive of the purchasing decisions of the population at large. For neuroimaging to be useful as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
215
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(229 citation statements)
references
References 25 publications
9
215
2
3
Order By: Relevance
“…Although most of this work is conducted by and for corporations aiming to improve sales rather than share scientific knowledge, published academic studies have begun to lend some credence to the potential of neuromarketing. For example, when teenage subjects were scanned while listening to unfamiliar songs, the reward system activity evoked by the songs, but not the subjects' ratings of their likeability, was predictive of sales of the songs over the subsequent three years 61 . Prediction is also important outside of business.…”
Section: Review Researchmentioning
confidence: 99%
“…Although most of this work is conducted by and for corporations aiming to improve sales rather than share scientific knowledge, published academic studies have begun to lend some credence to the potential of neuromarketing. For example, when teenage subjects were scanned while listening to unfamiliar songs, the reward system activity evoked by the songs, but not the subjects' ratings of their likeability, was predictive of sales of the songs over the subsequent three years 61 . Prediction is also important outside of business.…”
Section: Review Researchmentioning
confidence: 99%
“…In comparison to the self-report ratings of the individuals from the smaller groups, neural activity in MPFC added significant predictive value in both studies. Similar methods have been used to predict population level sales data for songs (Berns & Moore, 2012), perceived effectiveness of anti-drug messages (Weber, Huskey, Mangus, Westcott-Baker, & Turner, in press), and social media response to television content (Dmochowski et al, 2014). These studies differ markedly from those described above in that they treat the message (or other communication content) as the unit of analysis, and compare aggregated neural activity across multiple individuals as predictors of population level behaviors that presumably result from campaign exposure.…”
Section: Neural Variables As Moderatorsmentioning
confidence: 99%
“…Indeed, neuroscientists have suggested that endophenotypes carry the potential to characterize underlying traits and abnormalities independently of behavioral phenotypes (5). This stance has been supported by recent functional MRI (fMRI) studies that have, for instance, accurately predicted choices in a motor-decision task (6), substance abuse relapse (7)(8)(9)(10), and consumer purchases (i.e., neuromarketing) (11). These results raise the possibility that more direct measures of brain activity associated with impulse control may lend incremental utility to the prediction of future antisocial behavior.…”
mentioning
confidence: 97%